DETERMİNANTS OF FOREİGN PORTFOLİO INVESTMENT: THE CASE OF TÜRKİYE (Third Sector Social Economic Review, 2024)
This study aims to empirically investigate the short and long-run relationship between foreign portfolio investments and macroeconomic variables in Türkiye. In this context, the ARDL bounds test is applied to quarterly time series data on non-residents' equity investments, exchange rate, interest rate, consumer price index, gross domestic product, and S&P 500 index for 2006-2023. The findings reveal a cointegration relationship between foreign portfolio investments and macroeconomic factors. In the long run, consumer price index and exchange rate variables cause foreign portfolio investment. On the other hand, according to the error correction model results, GDP and the S&P 500 index are statistically significant determinants in the short run. The study results provide empirical evidence on the factors that significantly impact foreign portfolio investment in Türkiye and reveal the importance of a stable macroeconomic environment for attracting portfolio investment.
Keywords: Foreign portfolio investment; ARDL bounds test; Türkiye; Macroeconomic Factors; Emerging markets